تفعيل وسائل وسلطات الضبط الاداري في مكافحة جائحة كورونا - بوعكاز, ايمان; مشحاط, ليندة (جامعة الوادي university el-oued, 2021)
بعد انتشار فيروس كورونا المستجد، وتصنيفه من قبل الصحة العالمية وباء عالميا لاجتياحه جميع دول العالم وتأثيره على كافة المجالات، وجدت الدول نفسها مجبرة على اتخاذ تدابير ضبطية مقيدة لممارسة بعض الحقوق والحريات الأساسية للأفراد لمواجهة الوباء. وتمثلت هذه الآليات القانونية المتخذة من قبل السلطات المختصة في الجزائر، في آلية تقييد الحريات والحقوق وفق ما يتكيف مع الوضع الاستثنائي للحد من انتشار الوباء من جهة ومن جهة أخرى لحماية الحق في الصحة العامة، وآلية التجريم الوقائي لإعطاء فعالية للتدابير المتخذة من قبل السلطات والمفروضة على كافة الأفراد بصفة عامة أو بصفة خاصة، وفقا لمجموعة من المراسيم التنظيمية ونصوص مواد قانونية مستحدثة.After the spread of the new corona virus, and its classification as a global epidemic by the world health organization, for the raison of its invasion of all countries of the world and its impact an fields. Countries found themselves forced to take restrictive operations to do some basic rights and freedoms. These legal mechanisms taken by the comptent authorities in Algeria consisted in restricting freedoms and rights in accordance with what adapts to the exceptional situation, to limit the spread of the epidemic on the one hand and on the other hand to protect the right to public health, and the preventive criminalization mechanism to give effectiveness to the measures taken by the authorities and imposed on all individuals in general or in particularof individuals to confront the epidemic. These legal mechanisms taken by the competent authorities in Algeria consisted in restricting freedoms and rights in accordance with what adapts to the exceptional situation, to limit the spread of the epidemic on the one hand and on the other hand to protect the right to public health, and the preventive criminalization mechanism to give effectiveness to the measures taken by the authorities and imposed on all individuals in general or in particular according to a set of regulatory decrees and texts of updated legal articles.
مذكرة ماستر